Relationship between Parenting Educational Styles and Well-Being in Families with Autistic Children: A Systematic Review - Elena Benseny Delgado; Wenceslao Peñate Castro; Alicia Díaz Megolla (MDPI AG, 2024)
The prevalence of diagnosed cases of autism has increased rapidly, which has raised interest in studying the variables related to the well-being of these families. The purpose of this paper is to review the recent literature on other variables related to family well-being, such as parenting styles. We conducted a systematic review using the PRISMA check list and bias assessment with the aim of analyzing if the concepts of autism, well-being and parenting style are related. We screened 755 references from relevant databases like Scopus, Pubmed, PscyInfo EBSCO, Web of Science and Dialnet, updated on May 2024. Sixteen full text articles and abstracts were read. It was identified that the authoritative parenting style, as well as those based on warmth, establishing relationships and emotional bonding, and low expressed emotion were positively related to family well-being. On the other hand, authoritarian, permissive and overprotective styles, as well as critical, punishing and training-based, were negatively associated with well-being and quality of family life.